Dynamics of clinical manifestations and cytokine concentrations in rheumatoid arthritis patients on tofacitinib therapy - N. A. Lapkina; A. A. Baranov; N. E. Abaytova; N. Yu. Levshin; A. S. Avdeyeva; E. A. Leontyeva; A. S. Artyukhov; E. L. Nasonov (Научно-практическая ревматология, 2021)
Objective - to study the dynamics of clinical and laboratory parameters of inflammatory activity of the disease and cytokines in rheumatoid arthritis (RA) patients on a background of tofacitinib (TOFA) treatment.Material and methods. Ten patients with a reliable diagnosis of RA have been examined: patients' age was 51.0 (48.0; 62.0) years, duration of disease was 7.0 (3.0; 20.0) years. All patients had high disease activity: DAS28 -5.88 (5.53; 5.94), CDAI - 33.0 (29.0; 36.0), SDAI - 33.72 (30.75; 36.85). All patients were treated with TOFA at a dose of 5 mg 2 times a day on a background of methotrexate therapy, non-steroidal anti-inflammatory drugs, and glucocorticoids. Observations were performed before treatment and after 3 and 6 months of therapy. Serum levels of 15 cytokines (IL-1β, IL-4, IL-6, TNF-α, INF-γ, IL-10, IL-17A, IL-17F, IL-21, IL-22, IL-23, IL-25, IL-31, IL-33, sCD40L) were examined using multiplex xMAP technology.After 3 and 6 months of TOFA therapy, there was a significant decrease in DAS28 of 4.55 (3.47; 5.16) and 3.92 (3.80; 4.60); CDAI - 16.5 (11.0; 23.0) and 18.0 (15.0; 19.0); SDAI - 16.6 (11.23; 23.06) and 18.07 (15.06; 19.10); ESR - 19.0 (11.0; 26.0) and 7.0 (4.0; 18.0); CRP - 0.56 (0.50; 1.99) and 0.71 (0.51; 1.1) respectively. IL-6 levels decreased after 3 and 6 months of therapy (p<0.05). The concentration of INF-γ significantly decreased after 3 months (p<0.05), but remained unchanged thereafter. Concentrations of IL-25 and IL-31 decreased after 3 months (p<0.05), and by the 6th month of treatment there was an increase, however, not reaching the initial values.Conclusion. The results of the study show the efficacy of TOFA in RA and create prerequisites for further study of the cytokine-dependent mechanisms of inflammation in this disease.